THE PECULIARITIES OF CEREBRAL BLOOD FLOW IN PATIENTS WITH CHRONIC HEPATITIS - V. E. Kulikov; B. B. Fishman; A. V. Volkov; G. S. Malyutin; G. I. Shvartsman (Столичная издательская компания, 2015)
Aim. To study extra- and intracranial hemodynamics in patients with chronic hepatitis of different activity.Material and methods. Ultrasonography of the cerebral blood flow was performed in 576 patients with chronic hepatitis.Results. Contralateral hemyspherical asymmetry (more than 30 %) of the maximum linear rate of blood flow in the medium cerebral arteries and decrease in resistance index (0,55±0,09) and pulsativity index (1,34±0,66) were found in 33,8 % of patients with chronic hepatitis of high activity. Collateral blood flow reduction through connecting arteries of Willis circle was revealed in 13,8 % of patients. The tortuosity of arteries and thickening of intima-media complex was found in patients with chronic hepatitis (mainly of high activity). It leads to decline of cerebral blood flow.Conclusion. Symptomatic and asymptomatic cerebral blood flow disturbances were observed in 23,2% and 38,8% of patients with active chronic hepatitis respectively.